An assessment of trade performance and competitiveness of OECS countries - Vignoles, Christopher (Caribbean RNM/IDB Project HastingsBB, 2005)
Looks briefly at the importance of trade for the economies of the OECS sub-region. Analyses the performance of services and merchandise trade. Provides insights into the competitiveness of sectors and products in both categories of trade. Identifies the cost structures faced by firms operating across the OECS. Assesses the impact on competitiveness in production and trade. Suggests a strategy for competitiveness to drive sustainable export-led growth in the region.